2015
DOI: 10.5713/ajas.15.0241
|View full text |Cite
|
Sign up to set email alerts
|

Is Hiding Foot and Mouth Disease Sensitive Behavior for Farmers? A Survey Study in Sri Lanka

Abstract: Foot and mouth disease (FMD) has a long history in Sri Lanka and was found to be endemic in various parts of the country and constitutes a constant threat to farmers. In Sri Lanka, currently there is no regular, nationwide vaccination programme devised to control FMD. Therefore, improving farmers’ knowledge regarding distinguishing FMD from other diseases and ensuring prompt reporting of any suspicion of FMD as well as restricting movement of animals are critical activities for an effective FMD response effort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…While this study used a proxy for known truth by directly observing adherence data after the survey was completed, they did not directly observe the retrospective adherence behavior asked about in the survey. Evidence in low and middle-income countries is similarly mixed and limited, with only two published studies identified using LR [ 14 , 15 ], only one of which, TN Randrianantoandro, et al [ 14 ], compared results with direct questioning. The item count process may be cognitively and logistically difficult in comparison with direct questionnaires, as LR introduces additional opportunities for error due to lack of education, language, and cultural appropriateness of both the sensitive and non-sensitive questions [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…While this study used a proxy for known truth by directly observing adherence data after the survey was completed, they did not directly observe the retrospective adherence behavior asked about in the survey. Evidence in low and middle-income countries is similarly mixed and limited, with only two published studies identified using LR [ 14 , 15 ], only one of which, TN Randrianantoandro, et al [ 14 ], compared results with direct questioning. The item count process may be cognitively and logistically difficult in comparison with direct questionnaires, as LR introduces additional opportunities for error due to lack of education, language, and cultural appropriateness of both the sensitive and non-sensitive questions [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…FMD is the most damaging viral disease affecting cattle farming in Sri Lanka. Thus, the Sri Lankan government has prioritized FMD, among all other livestock diseases, to be eradicated by 2020 [ 20 ]. Despite the severity of the disease, only a limited number of attempts have been made in Sri Lanka to track the origins of outbreaks and to determine the lineage and topotype of circulating viral strains.…”
Section: Discussionmentioning
confidence: 99%
“…After 2009 no in-depth studies on Sri Lankan FMDV have been published except for a few field surveys and characterizations by World Reference Laboratory for FMD (WRLFMD) reports [ 18 , 19 ]. A massive FMD outbreak occurred in Jaffna in December 2013, and quickly spread into lower northern regions and subsequently to the other parts of the country by 2014 [ 20 ]. Department of Animal Production and Health (DAPH) of Sri Lanka reported 58,645 infected cattle and 1,265 deaths in 2014 [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some recent contributions, although not exhaustive, cover a great variety of topics. For instance: the measure of the impact of HIV/AIDS infection in Botswana (Arnab & Singh, ); the assessment of sensitive health‐risk behaviors in HIV/AIDS positive individuals (Arentoft et al., ); the assessment of permissive sexual attitudes and high‐risk sexual behaviors to reduce the transmission and acquisition of sexually transmitted infections and HIV/AIDS (De Jong, Pieters, & Stremersch, ; Starosta & Earleywine, ; Geng, Gao, Ruan, Yu, & Zhou, ; Kazemzadeh, Shokoohi, Baneshi, & Haghdoost, ); patterns of condom use among university students for HIV/AIDS control programs (Safiri, ; Vakilian, Mousavi, Keramat, & Chaman, ); the prevalence of sexual behaviors such as extradyadic sex (Tu & Hsieh, ), commercial sex among homosexual men (Chen et al., ) and sexual assault (Krebs et al., ); the use of drug, and athletic, cognitive, and mood performance‐enhancing substances (Striegel, Ulrich, & Simon, ; Petróczi et al., ; Dietz et al., 2013; Franke et al., ; James, Nepusz, Naughton, & Petróczi, ; Nakhaee, Pakravan, & Nakhaee, ; Stubbe, Chorus, Frank, de Hon, & van der Heijden, ; Shamsipour et al., ; Khosravi et al., ; Cobo, Rueda, & López‐Torrecillas, ); smoking behavior validation studies (Fox, Avetisyan, & van der Palen, ); dental hygiene habits of Chinese college students (Moshagen, Musch, Ostapczuk, & Zhao, ); farmers' transgressionary behaviors and prevalence of animal diseases such as sheep scab in Wales (Cross, Edwards‐Jones, Omed, & Williams ), African swine fever in Madagascar (Randrianantoandro, Kono, & Kubota, ), or foot and mouth disease‐infected animals in Sri Lanka (Gunarathne, Kubota, Kumarawadu, Karunagoda, & Kon, ); estimation of the prevalence of induced abortion (Oliveras & Letamo, ; Moseson et al., ; Perri, Pelle, & Stranges, ); ecological and biological conservation issues including estimation of illegal bushmeat hunting (Nuno, Bunnefeld, Naiman, & Milner‐Gulland, ; Conteh, Gavin, & Solomon, ), illegal fishing (Blank & Gavin, ; Arias & Sutton, ), and unauthorized natural resources use (Harrison, Baker, Twinamatsiko, & Milner‐Gulland, ).…”
Section: Introductionmentioning
confidence: 99%